(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2021)
Abstract — Blockchain technology plays an important role in the business development. Many businesses can possibly benefit from the novelties blockchain decentralization expertise and confidentiality procedures offer with regard to make safe, information access, inspecting and handling dealings within digital platforms. This research work delivers understandings into the existing growths within blockchain expertise. It examines and delivers insights into the safety of blockchain applications by review. This research work suggests likely solutions in detail for improving the safety of the blockchain for business applications.